2020
DOI: 10.2174/1381612826666200518105633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Botulinum Toxin on Equinus Foot Deformity in Cerebral Palsy Patients: A Systematic Review and Network Meta-analysis

Abstract: Background: Cerebral palsy (CP) is a brain disorder that affects the development of movement and posture leading to limitation of Range of Movement (ROM) in the growing children. CP leads to deformities as equinus foot deformity. We aim to investigate the efficacy of different botulinum toxin (BTX) products with or without serial casting in reducing the muscle spasticity in equinus foot deformity in patients with CP. Methods: A systematic review of the literature was performed via searching of the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The possible explanation may be from heterogeneity caused by gait assessment scales, small number of studies, and baseline passive ankle dorsiflexion. On the contrary, the network meta-analysis found that BoNT-A significantly improved passive ankle dorsiflexion with knee extension at 3 months compared to BoNT-A plus casting [18]. These inconsistent results may be due to The AFO was known to enhance ankle dorsiflexion during walking.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The possible explanation may be from heterogeneity caused by gait assessment scales, small number of studies, and baseline passive ankle dorsiflexion. On the contrary, the network meta-analysis found that BoNT-A significantly improved passive ankle dorsiflexion with knee extension at 3 months compared to BoNT-A plus casting [18]. These inconsistent results may be due to The AFO was known to enhance ankle dorsiflexion during walking.…”
Section: Discussionmentioning
confidence: 98%
“…BoNT-A can improve gait pattern measured by PRS and VGA with minor side effects when compared to placebo [17]. BoNT-A plus delayed casting might be the best treatment to improve ankle dorsiflexion at stance, while BoNT-A alone was at the highest rank for passive ankle motion at knee extension, followed by immediate casting, BoNT-A plus delayed casting, and BoNT-A with immediate casting [18]. However, none of them showed significantly a different peak dorsiflexion at stance and passive ankle motion [18].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Botulinum neurotoxin (BoNT), produced by Clostridium botulinum, is the most potent toxin; [5] it is a zinc protease that acts through the cleavage of neuronal vesicle-associated proteins responsible for the release of acetylcholine into the neuromuscular junction [6]. While there are seven biological serotypes of BoNT, only two are used in clinical practice [7]: BoNT serotypes A and B are used for a variety of medical indications, including facial wrinkles, dystonia, spasticity, migraines, multiple sclerosis, post-stroke gait disorders, and cerebral palsy deformities [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%